Evaluation Framework of City's Carbon Emission Reduction Responsibility. (May 2017) - Shuai, Geng; Chongqing, Xu; Lijun, Lin; Shoucheng, Zhang; Guihuan, Yan
Abstract: In order to carry out the emission reduction commitment, the China's provinces must undertake certain carbon emission reduction (CER) tasks and the basic CER units are the cities of these provinces. But the actual question is how to allocate the CER tasks to the cities reasonably, in other word, how to determine their CER responsibilities. So in this paper, we established CER responsibility evaluation index system from five attributes, namely, CER potential, CER cost, strategic positioning, economic level, low carbon level, social stability and then established a evaluation framework of CER responsibility based on Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The innovation points are as follow: the city's CER responsibility is evaluated from more comprehensive perspectives, so the result will be more reasonable; the evaluation framework of CER responsibility is easy to use and can deeply analyzes the merits and demerits of the city in the CER responsibility. Finally, a case study is demonstrated to provide the decision framework can effectively handle such a complicated problem and lead to an outstanding result.